Building Community Collaboration in the Development of a Standard. Issue 1 (1st May 2022) - Estelle, Lorraine
ABSTRACT: COUNTER is the membership organization responsible for the Code of Practice, which enables publishers and vendors to count and report the use of electronic resources in a standard way. This article outlines how COUNTER members from the library and publishing communities worked together to develop Release 5 of the Code of Practice, and how they collaborate to support its adoption and use. It describes how COUNTER members continue to cooperate on new developments such as the reporting of Open Access usage which cannot be attributed to institutions.